Network and entrepreneur firm success: religious practice as moderator - Abdul Wahab, Nadratun Nafisah; Md Hussain, Muhammad Nasri; Abdul Ghani, Abdullah (JHLCB, 2017)
This article discusses about network factor to the firm success and the entrepreneur religious practices included as a moderator factor. The concept under discussion is based on the new model of strategic/tactical behaviour of the SME owner managers by Simpson and colleagues (2013). This concept will be used for future research to determine the relationship within these variables in a model. Based on the recent study, there are relationship between network and entrepreneur’s firm success. Whereas from past study found that religious practice can moderate the entrepreneur’s firm success. Therefore, this article proposes that entrepreneur’s firm success study can be conducted in the future along with religious practices.